The Acute Hangover Scale: A New Measure of Immediate Hangover Symptoms - Rohsenow, Damaris J. (2006)
PURPOSE: No psychometrically established measure of acute hangover symptoms is published and available to use in experimental investigations. The present investigation combined data across three studies of residual alcohol effects to establish the properties of a new Acute Hangover Scale (AHS) based on symptoms supported in previous lab studies. METHODS: Professional mariners from a Swedish maritime academy (n = 54) and young adult students/recent graduates of urban U.S. universities (n = 135) participated in one of three within-subjects' studies of residual effects of heavy drinking (M = .114 g% breath alcohol concentration [BrAC]). All drank placebo one evening and alcoholic drinks another evening followed by an 8-hour sleep period before completing the AHS 10-20 min after awakening. RESULTS: The AHS showed excellent internal consistency reliability the morning after alcohol. The AHS mean score and each item were significantly affected by beverage but not demographics or typical drinking, supporting validity. CONCLUSIONS: The AHS is a reliable and valid instrument for assessing acute hangover symptoms in experimental investigations of residual alcohol effects.